TAXONOMIC DIVERSITY OF FERNS OF TWO RECREATIONAL FORESTS IN KEDAH, MALAYSIA: Checklists of Ferns of Forests in Kedah, Malaysia - Akomolafe, Gbenga Festus; Rahmad, Zakaria (Malaysian Journal of Science, 2019)
The paucity of published data on the diversity and richness of ferns in Bukit Hijau recreational forest and Sungai Sedim forest in Kedah, Malaysia, prompted this study. This was to provide a baseline checklist of the ferns in these two forests. We conducted a field survey covering a distance of about 4000 m from the entrance of the forests. Preferential non-random sampling was employed, whereby all the encountered ferns were collected and identified. The incidence data were used to estimate the species richness and diversity indices through rarefaction and extrapolation analysis. It was observed that Bukit Hijau forest was more abundant in fern species and more diverse than Sungai Sedim forest. A total of 44 ferns were documented at Bukit Hijau forest while 28 were observed at Sungai Sedim forest with the family Polypodiaceae dominating the two forests. Thirteen ferns were observed to be similar in the two forests, thereby giving a Sorensen similarity index of 36.11%. Data on the IUCN conservation status of 56 ferns out of 58 were lacking. Suitable microhabitat conditions such as abundant moisture and low light intensity may be responsible for the higher richness of ferns at Bukit Hijau forest than Sungai Sedim forest. Future study is needed in relating the presence of the ferns with environmental gradients to better understand the conditions enhancing the ferns of these two forests.